2017
DOI: 10.1080/03098265.2017.1290590
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing critical thinking skills in first year environmental management students: a tale of curriculum design, application and reflection

Abstract: This paper chronicles the experience of academic staff in developing a course to enhance the critical thinking skills of environmental management undergraduates. We outline our considerations and process for course development, discuss insights from course evaluations, and reflect on the challenges encountered. We believe these perspectives will be useful for others who are developing critical thinking skills curricula, especially first year courses. Aspects of the course design which were considered particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…CAT is based on item response theory, selects items from an item bank that are most appropriate for each child, thereby minimizing the number of items needed to ensure an accurate score (Huang, et.al, 2018: 2). This is also supported by the study of Whiley et. al (2017) which states that the development of students' critical thinking skill is affected by a good study environment management, e.g.…”
Section: Discussionsupporting
confidence: 86%
“…CAT is based on item response theory, selects items from an item bank that are most appropriate for each child, thereby minimizing the number of items needed to ensure an accurate score (Huang, et.al, 2018: 2). This is also supported by the study of Whiley et. al (2017) which states that the development of students' critical thinking skill is affected by a good study environment management, e.g.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the students' thinking structures will be more complex (Foster, 2009). The research by Whiley et al (2017) on the new students of environmental management in Queensland University found that before the students attended the lecture, they were given matriculation for a year relating to their critical thinking skills. This is because the student must be able to critically evaluate something in the workplace and society.…”
Section: Introductionmentioning
confidence: 99%
“…This definition is a modification of the interpretations suggested by Davies (2014), Facione (2000), and Watson and Glaser (2008) and they summarise all previous definitions and reflect the components of critical thinking referred to in this study. Davies (2013;, Hammersley-Fletcher and Hanley (2016), Simpson and Courtney (2009), Shin et al (2006), Whiley et al (2017) and others emphasise the importance of the development of critical thinking in settings of the vocational training at tertiary school. Since language training has become a part of both vocational training and professional competence, Edberg (2018), Pessoa et al (2018), Wilson (2016) draw attention to the importance of the development of critical thinking in the process of communication activity along with the development of receptive (reading) and productive (writing) speech skills that addresses the concept of ESP training that is supposed to combine both job-related skills training and language training simultaneously (Moore, 2017).…”
Section: The Concept Of Critical Thinking and Espmentioning
confidence: 99%